2014
DOI: 10.4172/2167-0943.1000166
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Diabetic Patient Perception on Diabetic Disease and Self-Care Practice in Dilla University Referral Hospital, South Ethiopia

Abstract: Background: Diabetes is a chronic and irreversible disease that lasts, lifelong, directly concerns any individual of all ages and their relatives, and brings heavy economic burden, affects self-care activities and shortens life expectancy due to the chronic damages it causes, Thus, before considering any possible intervention it was imperative to assess present knowledge, perception, and self-care practices of patients towards the management of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
7
10
0
Order By: Relevance
“…In this study, the magnitude of overall poor self-care practice was 45.7% (95% Cl 40.9–51%); which is consistent with studies conducted in Dilla University Hospital [19], Nekemte referral Hospital [10], Mekele and Ayder Referral Hospital, Ethiopia [20], and India [21] which were (44%, 45%, 49% and 50.5%) respectively. However, it is higher than a study conducted in Addis Ababa (39.7%) [21].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the magnitude of overall poor self-care practice was 45.7% (95% Cl 40.9–51%); which is consistent with studies conducted in Dilla University Hospital [19], Nekemte referral Hospital [10], Mekele and Ayder Referral Hospital, Ethiopia [20], and India [21] which were (44%, 45%, 49% and 50.5%) respectively. However, it is higher than a study conducted in Addis Ababa (39.7%) [21].…”
Section: Discussionsupporting
confidence: 90%
“…Respondents who had poor diabetes knowledge were also 5 times more likely to have poor self-care practice than those who had good diabetes knowledge. This finding was supported with the study conducted in Nekemte, Indian and Bangladesh [9, 10, 19]. …”
Section: Discussionsupporting
confidence: 86%
“…[33][34][35] This improved practice of self-care observed in the study is similar to other studies where there was remarkable improvement in attitude and knowledge among DM patients in Turkey after intervention. 36,38 Diabetes patients who are educated and counseled about knowledge and practice of selfcare helped to strongly take care of their activities. Selfcare interventions play fundamental roles in life-style, dietary and behavioural changes.…”
Section: Discussionmentioning
confidence: 99%
“…And this finding supported by several studies reported the past. 5,7,15,16 Some of the limitations encountered were lack of standard or clear dietary guidelines put in place for diabetes mellitus patients and recall bias may be introduced since the study participants may fail to remember their eating practice of the week.…”
Section: Discussionmentioning
confidence: 99%